Imaging the evolution of metallic states in a correlated iridate - Okada, Yoshinori; Walkup, Daniel; Lin, Hsin; Dhital, Chetan; Chang, Tay-Rong; Khadka, Sovit; Zhou, Wenwen; Jeng, Horng-Tay; Paranjape, Mandar; Bansil, Arun; Wang, Ziqiang; Wilson, Stephen D.; et al. (Nature materials, 2013)
Iridate materials are at present the focus of interest because the combination of strong spin–orbit effects and many-body electronic correlations makes their physics non-trivial. Now, the density of states of Sr 3 Ir 2 O 7 is mapped out spatially using scanning tunnelling microscopy and spectroscopy, yielding insights into the influence of nanoscale heterogeneities on the electronic structure. The Ruddlesden–Popper series of iridates (Sr n +1 Ir n O 3 n +1 ) have been the subject of much recent attention due to the anticipation of emergent phenomena arising from the cooperative action of spin–orbit-driven band splitting and Coulomb interactions 1 , 2 , 3 . However, an ongoing debate over the role of correlations in the formation of the charge gap and a lack of understanding of the effects of doping on the low-energy electronic structure have hindered experimental progress in realizing many of the predicted states 4 , 5 , 6 , 7 , 8 , 9 . Using scanning tunnelling spectroscopy we map out the spatially resolved density of states in Sr 3 Ir 2 O 7 (Ir327). We show that its parent compound, argued to exist only as a weakly correlated band insulator, in fact possesses a substantial ~ 130 meV charge excitation gap driven by an interplay between structure, spin–orbit coupling and correlations. We find that single-atom defects are associated with a strong electronic inhomogeneity, creating an important distinction between the intrinsic and spatially averaged electronic structure. Combined with first-principles calculations, our measurements reveal how defects at specific atomic sites transfer spectral weight from higher energies to the gap energies, providing a possible route to obtaining metallic electronic states from the parent insulating states in the iridates.